2017
DOI: 10.1016/j.bbmt.2016.12.632
|View full text |Cite
|
Sign up to set email alerts
|

Neurologic Complications after Allogeneic Hematopoietic Stem Cell Transplantation

Abstract: Neurologic complications after hematopoietic stem cell transplantation are frequently life-threatening, and their clinical management can be highly challenging. A wide spectrum of causative factors-including drug-related toxicities; infections sustained by virus, bacteria, or invasive molds; metabolic encephalopathy; cerebrovascular disorders; immune-mediated disorders; and disease recurrence-may lead to potentially lethal complications. Moreover, given that some neurologic complications are not uncommonly dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
47
1
5

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(56 citation statements)
references
References 130 publications
3
47
1
5
Order By: Relevance
“…37,[41][42][43][44] Our long follow-up period of 5 years allowed us to analyze the temporal profile of NCs after transplant and account for late complications that may not have been detected in prior studies. Consistent with previous studies, 4,43,44,64 we found a decreasing incidence of NC over time from transplant, with the majority of events occurring in the early post-transplant period (up to day +100).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…37,[41][42][43][44] Our long follow-up period of 5 years allowed us to analyze the temporal profile of NCs after transplant and account for late complications that may not have been detected in prior studies. Consistent with previous studies, 4,43,44,64 we found a decreasing incidence of NC over time from transplant, with the majority of events occurring in the early post-transplant period (up to day +100).…”
Section: Discussionsupporting
confidence: 92%
“…The objectives of the study were to describe the incidence and type of NCs associated with HCT, to determine risk factors associated with CNSC and to 1 Immunology Division, The Walter and Eliza Hall Institute of Medical Research, Parkville, Victoria, Australia; 2 Department of Medical Biology, The University of Melbourne, Parkville, Victoria, Australia; 3 Royal Brisbane and Women's Hospital, Herston, Queensland, Australia; 4 School of Medicine, The University of Queensland, Brisbane, Queensland, Australia; Disease status (AML/ALL only) determine the effect of CNSC on progression-free survival (PFS), overall survival (OS) and non-relapse mortality (NRM). Only CNSCs were included in these analyses as they were considered more likely to affect NRM, PFS and OS than peripheral neuropathy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Described CNS clinical manifestations at TA‐TMA presentation include PRES, confusion, drowsiness, headaches, hallucinations, and seizures. There are no characteristic imaging findings in patients with CNS involvement, and imaging findings consistent with PRES are present in only a minority of patients . To our knowledge, there are no reports of persistent neurologic deficits in survivors of TA‐TMA.…”
Section: Discussionmentioning
confidence: 95%
“…4 Drug toxicity, fungal infections, and immune-mediated disorders prevail among other etiological factors. 5 Furthermore, their severity varies from mild to fatal disorders. 4,6 Those complications need to be recognized first by transplanters-hematologists.…”
Section: Introductionmentioning
confidence: 99%